Features of risk assessment of energy saving projects - Kurbanov, F.; Yessengeldin, B.S.; Yermanova, А.А.; Zhanseitov, A.T. (BUKETOV BUSINESS REVIEW, 2019)
The article discusses the legislative and theoretical basics of risk management of energy-saving projects aimed at reducing the number of energy resources used. The authors highlighted a variety of risks that affect energy-saving projects: entrepreneurial, property, liability and other specific risks. The article defines the main directions of work on energy-saving projects, including certain types of energy-saving activities: project activities, procurement activities, research activities, organizational and technical activities, organizational and motivational activities, analysis and expert assessment. The authors developed an algorithm for managing the risks of energy saving projects, which consists of five stages (risk planning; risk identification; risk analysis; risk assessment methods; monitoring and risk management).A comparative analysis of the risk assessment methods used allowed the authors to distinguish two approaches: qualitative and quantitative. The authors recommended ways to improve the risk assessment of energy saving projects: to identify the main activities of energy saving projects; apply the main stages of the risk management algorithm, which determine the final effectiveness of energy-saving projects; take into account the interaction of consumers, energy companies and the state in the process of identifying and assessing risks; to determine the methodology for risk assessment for energy-saving projectsat the legislative level.